Diet influences on growth and mercury concentrations of two salmonid species from lakes in the eastern Canadian Arctic. (1st January 2021) - Chételat, John; Shao, Yueting; Richardson, Murray C.; MacMillan, Gwyneth A.; Amyot, Marc; Drevnick, Paul E.; Gill, Hardeep; Köck, Günter; Muir, Derek C.G.
Abstract: Diet, age, and growth rate influences on fish mercury concentrations were investigated for Arctic char ( Salvelinus alpinus ) and brook trout ( Salvelinus fontinalis ) in lakes of the eastern Canadian Arctic. We hypothesized that faster-growing fish have lower mercury concentrations because of growth dilution, a process whereby more efficient growth dilutes a fish's mercury burden. Using datasets of 57 brook trout and 133 Arctic char, linear regression modelling showed fish age and diet indices were the dominant explanatory variables of muscle mercury concentrations for both species. Faster-growing fish (based on length-at-age) fed at a higher trophic position, and as a result, their mercury concentrations were not lower than slower-growing fish. Muscle RNA/DNA ratios were used as a physiological indicator of short-term growth rate (days to weeks). Slower growth of Arctic char, inferred from RNA/DNA ratios, was found in winter versus summer and in polar desert versus tundra lakes, but RNA/DNA ratio was (at best) a weak predictor of fish mercury concentration. Net effects of diet and age on mercury concentration were greater than any potential offset by biomass dilution in faster-growing fish. In these resource-poor Arctic lakes, faster growth was associated with feeding at a higher trophic position, likely due to greater caloric (and mercury) intake, rather than growth efficiency. Graphical abstract: Image 1 Highlights: Age and diet best explained mercury concentrations of fishes in Arctic lakes. Long-term growth rates (length-at-age) were related to fish trophic position. Faster-growing fish had a higher trophic position and mercury concentration. Muscle RNA/DNA ratios indicated differences in short-term growth rates of fishes. Muscle RNA/DNA ratios were a poor predictor of fish mercury concentrations. Abstract : Age and diet, but not growth rate, are primary drivers of mercury concentrations in two salmonid fish species in Canadian Arctic lakes.